Diversity of the Amoebozoa and Ciliophora Groups in Non-Human Primates Kept Ex Situ and in Their Handlers in Different Institutions in Brazil - Dib, Laís; da Silva, Breno; Correa, Lais; Pissinatti, Alcides; Moreira, Silvia; Tavares, Maria Clotilde; Teixeira, Rodrigo [UNESP]; da Costa, André Luíz; Muniz, José Augusto; Junglos, Amauri; Hirano, Zelinda Maria; Dada, Aline; et al. (My University, 2025)
Parasitic infections in non-human primates (NHPs) kept ex situ can be caused by zoonotic protists like Balantioides coli and Entamoeba histolytica. In Brazil, little is known about these infections in neotropical species. This study aimed to identify Amoebozoa and Ciliophora groups in fecal samples through in vitro isolation and molecular analysis, mapping their distribution in Brazil. Among 511 NHP and 74 handler’s fecal samples, Amoebozoa were found in 61 (11.9%) NHP samples, and Ciliophora in 6 (1.2%). Amoebic cysts were present in 12 (16.2%) human samples. Iodamoeba sp. from S. xanthosternos, E. coli from a handler, and B. coli from P. troglodytes and A. guariba were isolated in vitro. Molecular techniques identified E. dispar (34.2%), E. histolytica (5.1%), E. hartmanni (26.6%), E. coli (15.2%), Iodamoeba sp. (12.6%), E. nana (8.9%), and B. coli (7.6%). Greater protist diversity occurred in northern and southeastern regions, with E. histolytica and B. coli detected in endangered species, such as Saguinus bicolor and Alouatta guariba. Protist overlap between humans and NHPs underscores zoonotic risks. This study presents the first molecular characterization of Amoebozoa and Ciliophora in neotropical NHPs kept ex situ in Brazil, highlighting the need for improved hygiene and management protocols in primate institutions.
Keywords: in vitro isolation; molecular characterization; protists; zoonosis